Carcass Characteristics of Commercial Broiler Chicks Affected by Probiotic Supplementation - Gopal Ray Bansal (Research Aspects in Agriculture and Veterinary Science Vol. 3, 2021)
The objective of this study was to evaluate the influence of probiotic on carcass characteristics of commercial broiler chicks. Two probiotic levels (without and with probiotic supplementation) were considered for the study. The experiment consisted of two replicates for probiotic groups. The carcass characteristics and Conformation traits of broiler was evaluated at 6th week of age. Data were analyzed on survivor and equal number of bird’s per subclass basis. Analysis of variance revealed that the difference between replicates were not significant for the different traits under study as such all subsequent analysis was performed on combined sex basis. Inclusion of probiotic showed the significant effect on males, females and on combined sex basis the results of present study on per cent shrinkage, per cent dressing, per cent giblet and on total per cent meat yield. Higher per cent yield was estimated for most of the carcass components in the control group than the diet supplemented with probiotic. The cut-up parts yield (leg, breast, back with neck & wings) more or less similar in control and probiotic supplemented dietary group and also the percentage was lower in probiotic supplemented diet than the control group. The proximate principles of the meat revealed that there was no effect of the treatments on moisture, fat and ash content. However, the protein content was reduced significantly in broilers diet containing Probiotics. The lactobacillus counts were recorded higher in probiotic fed groups than the control.